2020
DOI: 10.1029/2020gl089429
|View full text |Cite
|
Sign up to set email alerts
|

Summer PM2.5 Pollution Extremes Caused by Wildfires Over the Western United States During 2017–2018

Abstract: Using observations and model simulations (ESM4.1) during 1988–2018, we show large year‐to‐year variability in western U.S. PM2.5 pollution caused by regional and distant fires. Widespread wildfires, combined with stagnation, caused summer PM2.5 pollution in 2017 and 2018 to exceed 2 standard deviations over long‐term averages. ESM4.1 with a fire emission inventory constrained by satellite‐derived fire radiative energy and aerosol optical depth captures the observed surface PM2.5 means and extremes above the 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 63 publications
2
27
0
Order By: Relevance
“…Systemic impacts are also observed, including effects on pregnancy outcomes such as preterm birth [10]. Wildfire smoke significantly increases PM 2.5 levels in the air, spreading long distances from the source and remaining elevated for weeks [11,12]. Regardless of the source, increased levels of PM 2.5 in the air have adverse health effects such as increased cardiorespiratory morbidity and mortality and public health burdens [13,14], including cost and increased numbers of healthcare visits.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic impacts are also observed, including effects on pregnancy outcomes such as preterm birth [10]. Wildfire smoke significantly increases PM 2.5 levels in the air, spreading long distances from the source and remaining elevated for weeks [11,12]. Regardless of the source, increased levels of PM 2.5 in the air have adverse health effects such as increased cardiorespiratory morbidity and mortality and public health burdens [13,14], including cost and increased numbers of healthcare visits.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative comparisons between different fire emissions inventories remain scarce due to the variable transport models used in each study and the spatial/temporal averaging used for comparison to observations (Liu et al, 2020). However, a few recent studies have shown significant variability in aerosol emissions from fire emissions inventories and large discrepencies between observations and fire emissions inventory driven predictions of surface aerosol concentrations (Pan et al, 2020; Xie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…During widespread co-occurrence days in recent seasons (2015, 2017, 2018, and 2020), PM 2.5 concentrations averaged across all constituent grid cells experiencing PM 2.5 /ozone co-occurrence exceeded the Environmental Protection Agency (EPA) regulatory limit of 35 μg/m 3 on 13 individual days ( Fig. 2D , orange markers), peaking at 47.7 μg/m 3 on 3 September 2017 during a period of widespread fire activity and smoke conditions in the western US ( 25 ). Ozone concentrations averaged across the same grid cells on these days ( n = 13) ranged from 57 to 63 parts per billion (ppb) ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…1D ). The largest spatial extents of co-occurrence were observed in 2015, 2017, 2018, and 2020—coincident with hot, dry summers and widespread fire activity, including the largest burned areas across the western US wildland-urban interface ( 20 , 24 , 25 , 29 , 36 , 47 ). Increases in the frequency and spatial extent of co-occurrences are associated with an increasing trend in July to September population exposure of ~24.9 million person-days/year ( P < 0.001) in the western US during 2001 to 2020 ( Fig.…”
Section: Resultsmentioning
confidence: 99%